The Central Role of Schools in Promoting Death Education Interventions - Fagnani, Giuditta (ETHICS IN PROGRESS, 2022)
Avoidance of discussion about death is common in contemporary Western societies. Plenty of literature substantiates that (at the beginning of the sentence), the actual tendency toward death denial can produce many negative effects such as the suppression of death-related thoughts and emotions. Death Education aims to strengthen the psychological anchors that allow us to recognize the profiles of anguish, prevent the decompensating factors of pathological mourning and process the experiences of loss at all ages. The article aims to support the usefulness and use of Death Education interventions in schools and their central role in promoting these interventions.